Funding, power and community development - McCrea, Niamh ca. 20./21. Jh; Finnegan, Fergal ca. 20./21. Jh (Rethinking community development, 2019)
This edited collection critically explores the funding arrangements governing contemporary community development and how they shape its theory and practice